Audiovisual translation and audio description: history and development - Yeskindirova, M.Zh.; Zadorozhnaya, L.A.; Korogod, N.P. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The intensive development of technology in the twentieth century had a fundamental influence on the appearance of new opportunities for obtaining information. During the same period, the attitude towards people with disabilities that existed before that time was radically changed. All this has led to the emergence of audiovisual translation as a form of social translation. The article examines the historical and socio-cultural factors that led to the emergence and development of audiovisual translation in its form of implementation – audio description. Despite the fact that understanding of the importance of including people with disabilities in the social context came at the beginning of the twentieth century, when the first attempts were made to replace visual methods of obtaining information by blind or visually impaired people with descriptions, the first theoretical works on this topic began to appear only in the 70s of the twentieth century. Currently, there is an increased interest in the development and improvement of audiovisual translation. The main idea of the article is to describe the prospects for the development of audiovisual translation in the XXI century